Airbag base fabric and airbag containing the same

By using multi-layer film covering and lamination processing of polyamide resin on the base cloth for airbags, the problems of gas leakage and internal pressure retention under high pressure are solved, and the airtightness and storage properties are improved, which is suitable for multiple Type of airbag.

CN115052787BActive Publication Date: 2024-12-20ASAHI KASEI KOGYO KABUSHIKI KAISHA
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202180013163.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-02-07
Filing Date
2021-02-05
Publication Date
2024-12-20
Estimated Expiration
2041-02-05

AI Technical Summary

Technical Problem

The existing base cloth for airbags has gas leakage problems under high pressure, making it difficult to take into account both softness, lightness, storage and heat resistance, and the mesh of the sewing part leads to poor internal pressure retention.

Method used

The base cloth for airbags covered with a multi-layer film with an adhesive layer has high slip resistance, a small ratio of bending part thickness to overlap thickness, and good scratch count and breathability under high temperature and high humidity conditions. It is laminated and The use of polyamide resin ensures the adhesion and softness of the base cloth.

Benefits of technology

It achieves excellent airtightness and pressure resistance under high pressure, and has good storage and lightweight characteristics. It is suitable for use in side curtain type, pedestrian airbags and distal airbags, extending the internal pressure holding time.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115052787B_ABST
    Figure CN115052787B_ABST
Patent Text Reader

Abstract

As a fabric for airbags laminated with a film, a base fabric for airbags is provided, which is soft and lightweight, has good rubbing resistance after heat resistance / moisture heat resistance, and has excellent internal pressure retention of the airbag after sewing, and an airbag containing the same. The base fabric for airbags of the present invention is a base fabric for airbags in which at least one side of the fabric is covered with a multilayer film having an adhesive layer, and is characterized in that the average value of the slip resistance of the base fabric in warp and weft is 350N / 2.5cm or more.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a base fabric for an airbag constituting an airbag cushion used in an airbag device for alleviating the impact on a human body in a collision accident of an automobile or the like. Background Art

[0002] As a device for mitigating the impact on the human body caused by a collision accident of a vehicle such as a car, the installation of airbag devices in vehicles is being promoted. As an airbag device that expands due to gas during a collision to absorb and mitigate the impact on the human body, in addition to airbag devices for the driver's seat and airbag devices for the front passenger seat, the installation of airbag devices such as curtain airbags, side airbags, knee airbags, and rear airbags in vehicles is gradually becoming practical for protecting passengers. Furthermore, the following airbag devices have been proposed: in order to protect pedestrians, an airbag device composed of an airbag buffer that expands toward the outside of the vehicle compartment; in the event of a side collision toward the side opposite to the side where the car seat is set (the far side), a far side airbag device composed of an airbag buffer that restricts the passenger sitting in the opposite direction of the collision side from moving toward the collision side, etc.

[0003] The airbag cushion of these airbag devices is usually folded small and stored. When the sensor detects the impact of an accident and the airbag cushion is expanded, the folded airbag is pushed out by the gas generated in the inflator, and the airbag cushion breaks through the cover of the storage part and flies out, and fully expands, thereby blocking the human body.

[0004] In recent years, in order to enable airbag devices to cope with a wide range of collision conditions, the size of airbag shock absorbers has become larger, and there is a demand for compact and lightweight storage dimensions.

[0005] In addition, there is an increasing demand for improving safety by suppressing the leakage of deployment gas and maintaining internal pressure for a long time to extend the time of human restraint. In addition to airbags for the driver's seat and the front passenger seat that use vents to control gas pressure, it is particularly important to suppress the leakage of deployment gas for curtain airbags, pedestrian airbags, and far side airbags that do not have vents. For the base fabric for airbags, suppressing the leakage of gas from the base fabric mesh and sewn parts during high-pressure deployment has become a problem.

[0006] In recent years, in order to suppress gas leakage in airbags, silicone-coated base fabrics obtained by coating fabrics with silicone are generally used. However, base fabrics coated with silicone may be unevenly coated, and the internal pressure retention under high pressure may be insufficient due to silicone breakage caused by the mesh of the base fabric. In addition, when a large amount of silicone is applied to solve this problem, there is a problem that the weight per unit area and thickness of the base fabric increase, and the weight and storage performance of the airbag deteriorate.

[0007] On the other hand, the following Patent Document 1 proposes a base fabric for airbags laminated with a film. Since the fabric is covered with a continuous film, the internal pressure retention under high pressure is excellent, but compared with the silicone-coated base fabric, the base fabric is hard and the airbag buffer is poorly receivable due to the film raw material itself and the characteristics of lamination. In addition, if the film is made thinner for the purpose of softening, the adhesion and rubbing resistance may deteriorate, or pinholes may be generated due to the heat and pressure during hot lamination, and the internal pressure retention under high pressure may deteriorate.

[0008] Furthermore, both silicone-coated and film-laminated base fabrics have the following problems: when the airbag is deployed, the sewing part bears high pressure, the base fabric is pulled by the sewing thread and meshes are formed, and the internal pressure retention is deteriorated due to gas leakage. In addition, there is a tendency that the base fabric laminated with a film is easily stressed by the insertion of the sewing needle, and a part of the film is damaged and peeled off, which increases gas leakage.

[0009] Prior art literature

[0010] Patent Literature

[0011] Patent Document 1: Japanese Patent Application No. 2005-535488 Summary of the invention

[0012] Problem that the invention aims to solve

[0013] In view of the level of the above-mentioned background technology, the problem to be solved by the present invention is to provide a base fabric for an airbag that is soft and lightweight, has good storage properties, and has good high-pressure deployment properties after heat / humidity resistance, and further, to provide a base fabric for an airbag that is excellent in maintaining the internal pressure of the airbag after sewing.

[0014] Solutions for solving problems

[0015] The present inventors conducted intensive studies and repeated experiments to solve the above-mentioned problems. As a result, they unexpectedly found that a base fabric for an airbag having the following characteristics can solve the problems, thereby completing the present invention.

[0016] That is, the present invention is as follows.

[0017] [1] A base fabric for an air bag, wherein at least one surface of a woven fabric is covered with a multilayer film having an adhesive layer, and the average value of the slip resistance in warp and weft of the base fabric is 350 N / 2.5 cm or more.

[0018] [2] The base fabric for airbags according to [1] above, wherein a ratio of a thickness of a bent portion of the base fabric for airbags to a thickness of two sheets overlapped (thickness of bent portion / thickness of two sheets overlapped) is 2.0 or less.

[0019] [3] The base fabric for an airbag according to [1] or [2], wherein the base fabric for an airbag has a high pressure air permeability of 1.0 L / cm at 300 kPa. 2 / min or less.

[0020] [4] The base fabric for airbags according to any one of [1] to [3] above, wherein the base fabric for airbags has a scrub count of 600 or more after being treated under high temperature and high humidity conditions of 80°C and 95% for 400 hours.

[0021] [5] The base fabric for an airbag according to any one of [1] to [4], wherein the base fabric for an airbag has a cover factor of 1800 or more and 2400 or less.

[0022] [6] The base fabric for airbags according to any one of [1] to [5], wherein the base fabric for airbags has a static air permeability of 0.30 L / dm2 when a sewing needle passes through the base fabric for airbags. 2 / min or less.

[0023] [7] An airbag base fabric according to any one of [1] to [6] above, wherein, for a cross section obtained by cutting the warp yarn exposed in the surface of the airbag base fabric covered with a multilayer film at the center of the warp direction of the exposed portion, or a cross section obtained by cutting the weft yarn exposed in the surface of the airbag base fabric covered with a multilayer film at the center of the weft direction of the exposed portion, when observed using a SEM, and the distance from the bottom of the warp yarn or the weft yarn in the center in the width direction to the multilayer film surface is set as A, and the distance from the multilayer film surface at the end of the warp yarn or the weft yarn in the width direction to the height of the multilayer film surface in the center in the width direction is set as B, the base fabric cross-sectional thickness ratio B / A is greater than 0.2 and less than 0.6.

[0024] [8] The base fabric for an air bag according to any one of [1] to [7], wherein the weight per unit area of ​​the multilayer film is 5 to 30 g / m 2 .

[0025] [9] The base fabric for an air bag according to any one of [1] to [8] above, wherein the adhesive layer of the multilayer film comprises a polyamide-based resin.

[0026]

[10] The base fabric for an air bag according to [9] above, wherein the polyamide-based resin is a copolymerized polyamide.

[0027]

[11] The base fabric for an air bag according to [9] or

[10] , wherein the polyamide resin has a melting point of 100 to 160°C.

[0028]

[12] The base fabric for an air bag according to [9] or

[10] , wherein the polyamide resin has a glass transition temperature of 0 to 80°C.

[0029]

[13] An airbag comprising the base fabric for an airbag according to any one of [1] to

[12] .

[0030]

[14] A side curtain airbag comprising the base fabric for an airbag according to any one of [1] to

[12] .

[0031]

[15] A pedestrian airbag comprising the base fabric for an airbag according to any one of [1] to

[12] .

[0032]

[16] A distal airbag comprising the base fabric for an airbag according to any one of [1] to

[12] .

[0033] Effects of the Invention

[0034] If the airbag base fabric described in the present invention is used to make an airbag buffer, the mesh of the base fabric and the sewn parts under high pressure is suppressed, forming an airbag buffer with excellent air tightness and pressure resistance. In addition, an airbag buffer with excellent storage capacity and light weight is formed, making it an airbag base fabric that is particularly suitable for side curtain airbags, pedestrian airbags, and far side airbags that require internal pressure retention and storage capacity. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 This is a diagram for evaluating the thickness of the bent portion of the base fabric.

[0036] Figure 2 This is a diagram showing sample preparation for evaluating static air permeability after puncture by a sewing needle.

[0037] Figure 3 This is a schematic diagram of the base fabric cutting position when evaluating the base fabric cross-sectional thickness ratio using SEM.

[0038] Figure 4 This is a cross-sectional view of the base fabric after cutting when evaluating the cross-sectional thickness ratio of the base fabric using SEM.

[0039] Figure 5 1 is a top view of a side curtain airbag used in the embodiment. DETAILED DESCRIPTION

[0040] Hereinafter, embodiments of the present invention will be described in detail, but the present invention is not limited to these embodiments and examples, and can be arbitrarily modified within the scope of the gist of the present invention and its equivalents.

[0041] The base fabric for airbags of the present embodiment is a fabric in which at least one surface thereof is covered with a multilayer film, and is characterized in that an average value of the slip resistance in warp and weft of the base fabric is 350 N / 2.5 cm or more.

[0042] The total fineness of the fibers constituting the airbag base fabric is preferably 200 dtex to 600 dtex, and more preferably 300 dtex to 500 dtex. If the fineness is 200 dtex or more, the base fabric strength will not be insufficient, while if the fineness is 600 dtex or less, the deployment speed will not be slowed down. In addition, the lower the total fineness, the lower the hardness and unit weight of the base fabric can be.

[0043] The single yarn fineness of the fiber constituting the base fabric for airbags is preferably 2.0 dtex to 7.0 dtex, and more preferably 2.0 to 4.0 dtex. If it is above 2.0 dtex, the filaments will not be damaged by the sewing needle during sewing, and the strength of the sewing portion (the boundary between the expansion portion and the non-expansion portion) will not be reduced or damaged during deployment. On the other hand, if it is below 7.0 dtex, the air permeability will not increase and the deployment speed will not slow down. In addition, the smaller the single yarn fineness, the lower the hardness of the base fabric can be suppressed. Furthermore, the smaller the single yarn fineness, the lower the curling of the fabric, the flatter the surface, and the improved adhesion to the film. In addition, in order to flatten the fabric, a single yarn with a cross-sectional shape such as a flat, triangular, pentagonal or other polygonal shape can be used.

[0044] From the viewpoint of taking into account mechanical properties, internal pressure retention and hardness, the cloth coverage factor (CF) of the base cloth for airbags is preferably 1800 to 2400, more preferably 1900 to 2300, and further preferably below 2200. If the cloth coverage factor is above 1800, the base cloth strength and air tightness required for the airbag can be obtained. On the other hand, the smaller the cloth coverage factor is below 2400, the softer the base cloth becomes. In addition, the smaller the cloth coverage factor is, the lighter the weight per unit area of ​​the base cloth becomes, so it is preferably below 2400. It should be noted that the cloth coverage factor (CF) is expressed by the following formula.

[0045] CF=√(d)×(2×W)

[0046] {Wherein, d is the average total fineness of the warp and weft constituting the yarn (dtex), and W is the average weave density of the warp and weft (roots / 2.54 cm).}

[0047] It should be noted that the cover factor of the base fabric for an air bag refers to the cover factor of the fabric constituting the base fabric.

[0048] The base fabric for airbags of the present embodiment is a fabric obtained by covering a woven fabric with a multi-layer film. The film is preferably covered by lamination.

[0049] The multilayer film covering the fabric is composed of at least two layers, wherein the layer bonded to the fabric is called an "adhesive layer" and the layer that is the film surface of the airbag base fabric and exposed to the outermost surface is called an "outer layer".

[0050] The multilayer film may be a two-layer structure of an adhesive layer / outer layer stacked with an adhesive layer and an outer layer, or a three-layer structure of an adhesive layer / intermediate layer / outer layer, or a five-layer structure of an adhesive layer / adhesive layer / intermediate layer / adhesive layer / outer layer. In addition, other layers other than the above may be further included. The multilayer film will be described below.

[0051] (Adhesive layer)

[0052] The adhesive layer is a layer that is melted and softened by the heat from the heating roller during the hot lamination process and adheres to the surface of the fabric. From the viewpoint of adhesion, adhesiveness and flexibility, the adhesive layer preferably contains a resin (referred to as "resin A" in this specification) having a glass transition temperature of 0 to 80°C and a melting point of 100 to 160°C. In addition to the resin A, the adhesive layer may also contain other resins (referred to as "resin B" in this specification). The resin A and the resin B may each be one or more. The adhesive layer may be composed of only the resin A, or may further contain the resin B and the additives described below.

[0053] The glass transition temperature of the resin A is preferably 0 to 80°C, more preferably 10 to 70°C, and further preferably 20 to 60°C. When the glass transition temperature is above 0°C, the blocking resistance of the film can be further suppressed. In addition, it is also preferred from the viewpoint of suppressing the reduction of adhesion between the film and the fabric in a hot and humid environment and the scratch resistance of the airbag base fabric. Furthermore, it becomes a film and airbag base fabric with good folding assembly and less rebound. On the other hand, by setting the glass transition temperature to within 80°C, the softness of the airbag base fabric is excellent. In addition, the glass transition temperature can be measured by the method described in the examples described later.

[0054] When there are two or more types of resin A, the glass transition temperatures of the respective resins A may be the same or different.

[0055] The melting point of the resin A is preferably 100 to 160° C., more preferably 110 to 150° C., and further preferably 120 to 140° C. By setting the melting point to 100° C. or higher, the bonding strength with the base fabric can be maintained even in a high-temperature use environment, and the range of conditions such as temperature, pressure, and time during lamination (also referred to as a process window) can be widened, and a multilayer film with stable quality can be obtained. On the other hand, by setting the melting point to 160° C. or lower, the temperature required during lamination will not be too high, and the damage to the fabric and film caused by heat can be suppressed.

[0056] The melting point can be measured by the method described in Examples below.

[0057] When there are multiple types of resin A, the melting points of the resins constituting resin A may be the same or different. When multiple types of resin A are included and multiple melting peaks exist, the melting peak temperature on the high temperature side of resin A is preferably 100 to 160°C, more preferably 110 to 150°C, and even more preferably 120 to 140°C.

[0058] As the resin A, polyamide resins are preferred from the viewpoint of small changes in properties such as flexibility and adhesion with respect to changes in temperature and humidity in the use environment. Among them, as the polyamide resin, copolyamide (a-1), dimer acid polyamide (a-2), and thermoplastic polyamide elastomer (a-3) are preferred, and copolyamide (a-1) is more preferred from the viewpoints of flexibility, adhesion, internal pressure retention under high pressure, and cost.

[0059] Examples of the above-mentioned copolymer polyamide (a-1) include copolymer polyamides obtained by copolymerizing two or more monomer components known as monomer components constituting aliphatic polyamides (for example, monomer components constituting polyamide 6, polyamide 66, polyamide 610, polyamide 11, and polyamide 12), and examples include polyamide 6 / 66, polyamide 6 / 12, polyamide 6 / 11, and polyamide 6 / 66 / 11.

[0060] Examples of the dimer acid polyamide (a-2) include dimer acid polyamides using a raw material obtained by dimerizing fatty acids (unsaturated fatty acids having 18 carbon atoms (eg, oleic acid, linoleic acid, etc.) of natural vegetable oils.

[0061] Examples of the thermoplastic polyamide elastomer (a-3) include thermoplastic polyamide elastomers (including dimer acid-based thermoplastic polyamide elastomers) whose soft segments (amorphous phases) include polyethers and whose hard segments (crystalline phases) include polyamide components.

[0062] Among them, polyamide 6 / 12 is preferred from the viewpoint of being particularly excellent in flexibility, adhesiveness, and internal pressure retention under high pressure.

[0063] The viscosity of the polyamide resin used in the above-mentioned adhesive layer is 50 to 200 ml / g, more preferably 80 to 180 ml / g, and further preferably 100 to 150 ml / g. If the viscosity is 50 ml / g or more, the molten resin will not excessively penetrate into the fabric, causing the base fabric for the airbag to become too hard. On the other hand, if the viscosity is 200 ml / g or less, the adhesive layer penetrates into the single yarn on the surface of the fabric, and sufficient adhesion can be obtained due to the anchoring effect. It should be noted that the above-mentioned viscosity is a value calculated in accordance with ISO307, which is the viscosity when 0.5% by mass of the polyamide resin is dissolved in a 96% sulfuric acid aqueous solution.

[0064] The adhesive layer may contain the resin B in addition to the resin A. The resin B used in this case may preferably include acid-modified polyolefins, ionomers, thermoplastic polyamide elastomers, etc. From the viewpoint of flexibility and adhesion in a low temperature environment, the glass transition temperature is preferably 40°C or less, more preferably 30°C or less, and further preferably 20°C or less. In addition, the melting point is preferably in the range of 80 to 160°C.

[0065] The mass ratio of the resin B in the adhesive layer (100 mass%) is preferably 90 mass% or less, more preferably 80 mass% or less, and even more preferably 70 mass% or less, from the viewpoint of adhesiveness.

[0066] The adhesive layer may contain various additives such as anti-blocking agent, lubricant, crystal nucleating agent, flame retardant, antistatic agent, antioxidant, ultraviolet absorber, light stabilizer, colorant, filler, etc. as long as the practical properties such as adhesion are not impaired. Among them, from the viewpoint of further improving the blocking resistance of the adhesive layer, it is preferred to contain anti-blocking agent, crystal nucleating agent and / or lubricant, more preferably to contain anti-blocking agent and / or crystal nucleating agent, and further preferably to contain anti-blocking agent and crystal nucleating agent.

[0067] Examples of the anti-blocking agent include organic particles such as cross-linked polystyrene, cross-linked acrylic (PMMA) resin, and fluorine (PTFE) particles; and inorganic particles such as silica particles, kaolin, and calcium carbonate.

[0068] Examples of the crystal nucleating agent include talc, alumina, kaolin, and high melting point polyamide (for example, polyamide having a melting point exceeding 160° C.).

[0069] Examples of the lubricant include aliphatic amides and metal soaps.

[0070] From the viewpoint of adhesiveness and blocking resistance, the mass ratio of the resin A (e.g., copolymerized polyamide, etc.) relative to 100 mass % of the adhesive layer is preferably 10 mass % or more, more preferably 20 to 100 mass %, and even more preferably 30 to 100 mass %.

[0071] The mass ratio of the additive in the adhesive layer (100 mass %) is preferably 30 mass % or less, more preferably 20 mass % or less, and further preferably 10 mass % or less, from the viewpoint of adhesion and blocking resistance.

[0072] (Outer layer)

[0073] From the viewpoint of preventing the outer layer from sticking to the roller due to melting during the heat lamination process and preventing pinholes, the outer layer must be composed of a resin having a higher melting point than the adhesive layer.

[0074] The melting point of the resin used in the outer layer is preferably higher than the melting point of the resin A by 20°C or more, more preferably higher by 25°C or more, and further preferably higher by 30°C or more. The melting point of the resin used in the outer layer is determined based on the ease of fusion (adhesion) on the heating roller used in the step of laminating with the fabric. By using a resin having a melting point higher than the melting point of the resin A by 20°C or more, fusion on the heating roller is less likely to occur, and stable lamination can be achieved.

[0075] It should be noted that when the adhesive layer contains multiple resins A and / or the outer layer contains multiple resins, the above melting point means: among the melting peak temperatures belonging to the multiple resins contained in the layer, the melting peak temperature appearing on the highest temperature side is the processing melting peak temperature.

[0076] In addition, the outer layer becomes the outermost layer when laminated on the fabric, so the flexibility of the outer layer affects the flexibility of the laminated base fabric. Therefore, from the viewpoint of obtaining an outer layer excellent in flexibility, resistance to stress generated during folding, air tightness, resistance to sewing needle puncture, strength, flame retardancy, sliding properties, etc., polyamide resins and polyester resins are preferred.

[0077] Examples of the polyamide resin include the polyamide resins (a-1, a-2, and a-3) exemplified as the resin A contained in the adhesive layer. These may be used alone or in combination of two or more.

[0078] The polyester resin is preferably a thermoplastic polyester elastomer, and examples thereof include a type using a polyether component as a soft segment (polyether-polyester type) and a type using a polyester component as a soft segment (polyester-polyester type).

[0079] (Middle layer)

[0080] Examples of the intermediate layer include a layer formed from a single type or a composition blended with multiple types of polyolefin resins such as linear low-density polyethylene, low-density polyethylene, medium-density polyethylene, high-density polyethylene, and polypropylene, acid-modified polyolefin resins, polyolefin copolymer resins, polyolefin thermoplastic elastomers, and acid-modified polyolefin elastomers. From the viewpoint of flexibility, it is preferred that the intermediate layer contain a polyolefin copolymer resin and / or a polyolefin thermoplastic elastomer.

[0081] (Adhesive layer)

[0082] The above-mentioned adhesive layer is a layer used to bond the various layers of the multilayer film. For example, a layer formed by an acid-modified polyolefin resin containing a polar functional group such as acid-modified polyethylene, acid-modified polypropylene, etc. or / and a polyolefin thermoplastic elastomer, etc., and it is ideal to select it according to the requirements for heat resistance in the application.

[0083] The adhesive layer may be a layer composed of only one type of resin or a layer containing a plurality of types of resins.

[0084] (Multilayer Film)

[0085] The multilayer film is a film having at least two layers. The flexibility of the multilayer film affects the stowability of the airbag, and a base fabric laminated with a highly flexible film can achieve excellent performance in terms of compactness when the airbag is stowed.

[0086] It is further speculated that the resistance of the film generated when the base fabric undergoes expansion and contraction deformation increases according to the film thickness, which affects the number of times until peeling. Therefore, the thickness of the multilayer film is preferably 5 to 30 μm, more preferably 5 to 25 μm, and further preferably 5 to 20 μm. These ranges are determined based on the balance between strength and flexibility. When the thickness is 5 μm or more, the mechanical properties of the film are sufficient, and when the thickness is 30 μm or less, the flexibility becomes good.

[0087] The weight per unit area of ​​the multilayer film laminated to the base fabric for airbags is preferably 5 to 30 g / m 2 , more preferably 5 to 25 g / m 2 , more preferably 5 to 20 g / m 2 , particularly preferably 5 to 15 g / m 2 If the unit area weight of the film is 5g / m 2 On the other hand, if the unit area weight of the film is 30 g / m 2 Below, the base fabric will not be too hard.

[0088] It is preferred to cover the fabric with a film by lamination, but it is important to flatten the surface of the fabric before using the film to cover the fabric. By bonding the film to the fabric with a flat surface, the contact area between the film and the fabric is increased, and sufficient adhesion can be obtained without applying excessive heat and pressure during hot lamination, and the generation of pinholes can be suppressed. Since the generation of pinholes can be suppressed, it is easy to apply to thin films, and a base fabric for airbags with excellent softness can be obtained. In addition, since the fabric is flat, heat and pressure can be uniformly applied to the film during hot lamination, so the resin component of the film will not deeply penetrate and fill the fabric inside such as between the woven yarns, and a base fabric for airbags with good rubbing resistance can be obtained. Furthermore, with the help of the uniform thickness of the covered film, the stress caused by the sewing needle to the film can be dispersed, the local damage and peeling of the film can be reduced, and the sewing mesh when stress is applied to the sewing part is also suppressed, which can improve the internal pressure retention of the airbag buffer formed by sewing. The flattening method is not limited, but from the perspective of simplicity, a treatment based on calendering is preferred. The temperature during calendering is preferably 100° C. or higher and 220° C. or lower. If it is 100° C. or higher, the fabric structure after calendering can be maintained, and if it is 220° C. or lower, the fabric will not be thermally degraded.

[0089] The linear pressure during calendering is preferably 0.5 to 15 kN / cm. If the pressure is 0.5 kN / cm or more, the calendered fabric structure can be flattened and the adhesion to the film can be improved. On the other hand, if the calendering pressure is 15 kN / cm or less, the fabric becomes paper-like and does not become hard.

[0090] The calendering is preferably performed on one side of the fabric, that is, the laminated side. By performing calendering on one side of the fabric, the flatness necessary for adhesion with the film can be maintained, and the fabric becomes paper-like and can be prevented from becoming hard.

[0091] The surface of the fabric flattened by the heat of the lamination process may return to the surface state before the process. However, the laminated film layer covers the unevenness of the fabric surface while maintaining a substantially uniform film thickness.

[0092] The lamination method includes: a heat lamination method in which a heated roller is used to continuously laminat e the film in a roll-to-roll manner; a vacuum lamination method in which a pressure is reduced and a single lamination is performed, etc. It is preferred that the above-mentioned adhesive layer of the above-mentioned multilayer film and the above-mentioned synthetic fiber fabric (base fabric) are carried out at a temperature range of, for example, 120 to 160° C. The linear pressure during lamination is preferably 0.01 to 1.5 kN / cm. If it is 0.01 kN / cm or more, the adhesion between the film and the base fabric is exhibited, and on the other hand, if it is 1.5 kN / cm or less, the formation of pinholes in the film can be suppressed during lamination.

[0093] Preferably, the fabric is laminated immediately after being calendered, thereby reducing the situation that the film penetrates into the fabric between the woven yarns and causes the base fabric to become hard, so it is easy to fold. In addition, the thickness of the film covering the fabric can be avoided to be locally thinned, so even if it is subjected to local stress due to needle puncture, it can also be avoided that the film is damaged and peeled off.

[0094] The calendering and lamination processing of the fabric can be appropriately carried out within the aforementioned range, but in order to melt and soften the adhesive layer of the film during the lamination process to obtain sufficient adhesion to the fabric, it is preferably processed at a higher temperature than the calendering process, and in order to suppress pinholes in the film, it is preferably processed at a lower linear pressure than the calendering process.

[0095] The weight per unit area of ​​the base fabric for airbags of this embodiment is preferably 140 g / m 2 Above and 240g / m 2 Below. If 140g / m 2 If the mechanical strength of the base fabric is above 240 g / m 2 Below, the weight of the airbag will not be too heavy.

[0096] The average warp and weft value of the slip resistance of the airbag base fabric of the present embodiment is 350N / 2.5cm or more, preferably 400N / 2.5cm or more and 1000N / 2.5cm or less, and more preferably 450N / 2.5cm or more and 950N / 2.5cm or less. If the average warp and weft value of the slip resistance of the base fabric is 350N / 2.5cm or more, it can resist the mesh peeling when stress is applied to the base fabric, which is helpful for low air permeability under high pressure. The slip resistance of the airbag base fabric can be adjusted by using a processing method such as the bonding force obtained by chemical design between the aforementioned multilayer film and the fabric, and the substantial bonding area of ​​the film on the fabric surface increases. In order to improve the bonding force, it is preferred to select a copolymer polyamide in the composition design of the multilayer film, and set the fabric to polyamide fiber. In addition, as a processing method for increasing the bonding area between the film and the fabric surface, it is also preferred to perform calendering on the fabric for thermal lamination.

[0097] Furthermore, if the slip resistance of the base fabric for an airbag is large, the sewn airbag will expand, and the mesh of the base fabric when the sewing yarn is loaded can be reduced, which significantly contributes to improving the internal pressure retention of the airbag.

[0098] On the other hand, if the warp and weft average value of the slip resistance is 1000 N / 2.5 cm or less, sewing can be performed while suppressing the occurrence of extreme skipped stitches and wrinkles.

[0099] Even if the airbag base fabric of the present embodiment is exposed to the harsh environment under high temperature and high humidity for a long time, it is also necessary to withstand the bending caused by folding, the long-term automobile vibration, the friction when the airbag is deployed, etc. Therefore, for the internal pressure retention, scratch resistance (rubbing resistance) is very important. In order to improve the scratch resistance, not only the good adhesion of the film and the fabric is more important, but also the flexibility of the film itself and the local thinning of the film thickness and the uniform film thickness will not occur due to the local penetration of the film into the fabric, so that the rubbing stress will not be concentrated on the interface between the film and the fabric. The scratch resistance of the airbag base fabric of the present embodiment is more than 600 strokes (times), preferably more than 800 strokes, and more preferably more than 1000 strokes. In the case of less than 600 strokes (stroke), the peeling phenomenon problem of film peeling sometimes occurs. When installed in a car, the film surface is easily peeled off due to external forces or the film surface is easily peeled off due to high temperature and high pressure gas. As a result, the internal pressure of the airbag cannot be maintained satisfactorily when the airbag is deployed, and thus, the performance of protecting passengers may be abnormal during a vehicle collision.

[0100] In this embodiment, the ratio of the thickness of the bent portion when the airbag base fabric is bent to the thickness when two airbag base fabrics are overlapped (bend thickness / two overlap thickness) is 2.0 or less, preferably 1.8 or less, and more preferably 1.7 or less. If the ratio of the thickness of the bent portion when the airbag base fabric is bent to the thickness when two airbag base fabrics are overlapped is 2.0 or less, the volume of the airbag buffer when folded can be reduced to form an airbag with excellent storage properties. This thickness ratio is the result of a method of forming a soft fabric, a multilayer film being a lightweight film, setting the multilayer film to be soft in the composition design, and preventing the film from penetrating into the fabric such as between the woven yarns during the pasting process of the multilayer film to avoid hardening of the base fabric.

[0101] The static air permeability of the base fabric for airbags of the present embodiment when a sewing needle which has not passed through the yarn is passed through to open a hole is 0.50 L / dm 2 / min or less, preferably 0.40L / dm 2 / min or less, more preferably 0.30L / dm 2 / min or less. If the static air permeability after needle puncture is 0.50L / dm 2 / min or less, the gas leakage from the sewn part can be suppressed when the airbag is deployed. This is the result of the multilayer film being a lightweight film, the multilayer film being designed to be soft, and the thickness uniformity of the film covering the fabric being avoided to avoid local thinning of the film during the pasting process of the multilayer film, thereby avoiding local peeling.

[0102] The air permeability of the airbag fabric of the present embodiment at 300 kPa is 1.0 L / cm 2 / min or less, more preferably 0.8L / cm 2 / min or less, more preferably 0.7L / cm2 / min or less. If the air permeability of the base fabric at 300kPa is 1.0L / cm 2 / min or less, it is possible to suppress gas leakage from the mesh of the base fabric when the airbag is deployed, which is useful for airbag buffers that are deployed under higher pressure. This is the result of the high slip resistance and high scratch resistance of the airbag base fabric. The elements of suppressing the mesh through covering and suppressing local peeling caused by rubbing will suppress the covering peeling air permeability under high pressure load.

[0103] In the SEM cross-sectional observation of the width direction of the warp or weft of the airbag base fabric of the present embodiment, the distance from the yarn bottom of the width direction center of the warp or weft to the multilayer film surface is set as A, and the distance from the multilayer film surface at the width direction end of the warp or weft to the multilayer film surface height in the width direction center is recorded as B, B / A is more than 0.20 and less than 0.60, more preferably more than 0.25 and less than 0.55, and more preferably more than 0.30 and less than 0.50. If B / A is more than 0.20, the film is uniformly laminated along the base fabric surface, and the adhesive force and slip resistance become high. In addition, by making the film not partially penetrate into the curled groove, a soft base fabric can be formed. From the structure of the fabric, the upper limit of B / A is 0.60. The cross-section obtained by cutting the warp yarn exposed in the surface of the aforementioned airbag base fabric covered with the multilayer film at the center of the warp yarn direction of the exposed portion, or the cross-section obtained by cutting the weft yarn exposed in the surface of the aforementioned airbag base fabric covered with the multilayer film at the center of the weft yarn direction of the exposed portion, is observed using SEM.

[0104] It should be noted that if Figure 3 As shown in FIG. 1 , for the yarn observed by SEM, the center of the yarn direction in the exposed portion on the side covered with the multilayer film is set as the base fabric cutting position when evaluating B / A. In addition, the distance A to the surface of the multilayer film is set as: the width direction ends of the warp yarn or the weft yarn (at Figure 4 The distance B from the multilayer film surface at the width end of the warp or weft yarn to the height of the multilayer film surface in the width direction is set as Figure 4 The average of the distances at 12 or 12' in the figure. For B / A, any of the average values ​​obtained by measuring the warp or weft yarn 5 times respectively can be within the above range. It should be noted that, for the 5 measurement locations, it is preferred to measure the locations at least 10 cm apart. When the base fabric to be measured is small and it is impossible to ensure measurement locations at least 10 cm apart, the average of the values ​​obtained by measuring 5 times at different locations is used.

[0105] Example

[0106] Hereinafter, although an Example and a comparative example of this invention are given and it demonstrates concretely, this invention is not limited to the following example.

[0107] (1) Yarn fineness

[0108] The apparent fineness of the yarn taken out from the base fabric for an airbag regardless of the warp and weft was measured five times in accordance with Appendix H of JIS L1096:2010, and the average value was defined as the fineness (dtex) of the constituent yarn.

[0109] (2) Number of single yarns

[0110] The cross section of the airbag base fabric was observed using a scanning electron microscope (VE-9800 manufactured by KEYENCE), the number of filaments in ten weaving yarns was counted, and the number of filaments with the highest frequency among the ten was defined as the number of single yarns.

[0111] (3) Single yarn fineness

[0112] The fineness of the constituent yarn is divided by the number of filaments to obtain the single yarn fineness (dtex).

[0113] (4) Weight per unit area

[0114] The weight per unit area of ​​the base fabric for an air bag (including the multilayer film) and the multilayer film was determined from the mass per unit area measured in accordance with 8.3.2 of JIS L 1096:2010.

[0115] (5)Weave density

[0116] The measurement was performed in accordance with JIS L1096:2010 8.6.1 b) Method B using Appendix FA.

[0117] (6) Cover factor (CF)

[0118] The fabric cover factor (CF) of the airbag base fabric is calculated by the following formula:

[0119] CF=√(d)×(2×W)

[0120] {Wherein, d is the average total fineness of the warp and weft constituting the yarn (dtex), and W is the average weave density of the warp and weft (roots / 2.54 cm).}

[0121] (7) Slip resistance

[0122] Except for using a sample piece obtained by cutting the base fabric for airbag into a piece having a width of 25 mm and a length of 200 mm, the slip resistance was measured 5 times in each of the warp and weft directions according to ASTM D6479, and the average value of the 10 times was defined as the slip resistance.

[0123] (8) Scratching number after high temperature and high humidity heat treatment

[0124] The airbag base fabric was treated under high temperature and high humidity conditions of 80°C and 95% for 400 hours. Thereafter, a scratch tester (manufactured by Imoto Seisakusho) was used to measure the warp and weft 5 times in accordance with ISO5981, and the average value was set as the scratch number after high temperature and high humidity heat treatment. If the number of tests when the laminated body began to peel off from the base fabric was less than 1000 times, the value was recorded. If peeling did not occur even if it exceeded 1000 times, it was recorded as 1000.

[0125] (9) Ratio of the thickness of the curved portion of the airbag base fabric to the thickness of the two overlapping sheets

[0126] Use a thickness meter (FFA-10 manufactured by Ozaki Seisakusho) to measure the thickness of two stacked airbag fabrics in accordance with JIS L1019. Next, cut the airbag fabric into pieces with a width of 5 cm and a length of 10 cm to make a sample sheet. Fold the sample sheet once along the length direction so that the film surface or silicone surface is on the inside, clamp the folded portion of the sample sheet under a 3 cm × 6 cm metal plate, and load a weight for 30 seconds in such a way that the total weight together with the metal plate reaches 10 kg. Afterwards, use the same thickness meter, as Figure 1 As shown in the figure, the measuring head is set so that the curved part comes to the center line of the measuring head of the thickness gauge, and the value after 1 minute of stabilization is measured. The value obtained by dividing the thickness of the curved part by the thickness of the two overlapping base fabrics is calculated. For this measurement, the measurement is performed 5 times in each of the warp and weft directions, and the average value is set as the ratio of the thickness of the curved part to the thickness of the two overlapping base fabrics.

[0127] (10) High-pressure air permeability at 300 kPa

[0128] Capillary Flow Porometer CFP-1200AEX (manufactured by Porous Metrials, Inc.) was used to set the multilayer film surface or silicone surface of the airbag base fabric to the pressurized side, and the gas permeation rate at 300 kPa was measured according to the gas permeability test mode. This measurement was performed 5 times, and the average value was set as the high-pressure air permeability at 300 kPa.

[0129] (11) Static air permeability after sewing needle puncture

[0130] Install an organ needle (DPx17 (#21) on the LSC-8BL-1 manufactured by SEIKO SEWING MACHINE, and drill the needle holes in a straight line so that there is no sewing yarn and the pitch is 50 needles / 10cm. Figure 2The pinhole line is set so that it is located at the center of the measurement diameter of the static air permeability measuring machine (Frazier Permeameter FP-2 manufactured by Toyo Seiki Co., Ltd.) and the film surface or silicone surface of the airbag base fabric becomes the pressurized side. The air permeability at 500 Pa is measured 5 times in accordance with ISO9237, and the average value is set as the static air permeability after sewing needle puncture.

[0131] (12) Base fabric cross-sectional thickness ratio (B / A)

[0132] like Figure 3 As shown in FIG. 1 , the warp yarns exposed on the surface of the airbag base fabric covered with the multilayer film are cut at the center of the warp yarn direction of the exposed portion, and the base fabric cross section is observed using a scanning electron microscope (VE-9800 manufactured by KEYENCE). The schematic diagram of the base fabric cross section at this time is as follows: Figure 4 . From both ends of the warp yarn in the width direction ( Figure 4 In the embodiment of the present invention, the distance from the bottom of the yarn in the center (13) of the warp yarn (12, 12') to the surface of the multilayer film is set as A, and the distance from the surface of the multilayer film at the end (12 or 12') of the warp yarn in the width direction to the height of the multilayer film surface in the center of the width direction is set as B, and B / A is measured. The result is set as the average value of the values ​​obtained by 5 measurements. In addition, for the 5 measurement locations, locations at least 10 cm apart are measured respectively. It should be noted that, for the two ends (12 or 12') of the warp yarn in the width direction, the position of the left side surface of the warp yarn cross section located on the far left in the SEM image taken is set as 12, and the position of the right side surface of the warp yarn cross section located on the far right is set as 12'.

[0133] (13) Airbag internal pressure retention

[0134] Under the conditions of sewing yarn of 1400 dtex and needle number of 5.0 needles / cm, the sewing is done by double-row sewing with a width of 4 mm. Figure 5 Side curtain airbag of the shape shown and with a capacity of 24L.

[0135] Insert the inner tube into the side curtain airbag to guide the deployment gas from the gas supply port at the rear end toward the front inflation section and the rear inflation section. The inner tube uses a plain woven fabric made of polyamide 6.6 fiber, 700dtex / 105f, with a warp and weft of 38 strands / inch (2.54cm). The cloth is sewn into a cylindrical shape by double-row sewing with a 4mm width under the conditions of a sewing yarn of 1400dtex and a needle number of 5.0 needles / cm with a caliber that can be inserted into the gas supply port. The front end of the inner tube is open, and the sewing part is set to the upper side, and the notch for the gas supply of the rear inflation section is set to the lower side.

[0136] A pressure sensor is installed at the center of the protection part of the side curtain airbag. After that, it is set in the holder in a curtain shape without being folded, and a 2.0 mol stored gas inflator is installed at the gas supply port using a hose belt and deployed. The internal pressure retention rate from 50 msec to 200 msec is determined according to the following evaluation criteria (internal pressure at 200 msec / internal pressure at 50 msec×100).

[0137] <Evaluation Criteria>

[0138] Internal pressure retention rate is 80-100%: ○

[0139] Internal pressure retention rate is 50-79%: △

[0140] Internal pressure retention rate 0~49%:×

[0141] (14) Melting point of film raw materials

[0142] A sheet with a thickness of 150 μm was prepared using a press molding machine "P2-30T-400" manufactured by Toyo Seiki Seisaku-sho, Ltd., and the melting peak temperature obtained by DSC ("Diamond DSC" manufactured by Perkin Elmer) at a heating rate of 10°C / min was set as the melting point. It should be noted that regarding the press molding conditions, samples were collected under the following conditions.

[0143] (15) Glass transition temperature of film raw materials

[0144] A sheet with a thickness of 0.9 mm was produced using a press molding machine "P2-30T-400" manufactured by Toyo Seiki Seisaku-sho, Ltd., and the loss tangent tanδ was measured under the following conditions using a dynamic viscoelasticity measuring machine ("MCR301" manufactured by Anton-Paar), and the peak temperature of the loss tangent tanδ was set as the glass transition temperature.

[0145] ·Measurement mode: Torsion (measurement accessory: SRF10)

[0146] Sample: Thickness = 0.9 mm Width = 10 mm Measurement span = 38 mm

[0147] Normal force: -0.3N

[0148] Swing angle: 0.1%

[0149] Frequency: 1Hz

[0150] Heating rate: 2℃ / min

[0151] [Example 1]

[0152] (Multilayer Film)

[0153] The film is a multilayer film of 4 types and 5 layers including the layer structure (mass %) of "adhesive layer (20%) / adhesive layer (10%) / intermediate layer (50%) / adhesive layer (10%) / outer layer (10%)". The adhesive layer is made of a raw material obtained by dry-blending 11 mass % of CoPA1 (trade name "Ube Nylon 7128B" (manufactured by Ube Industries, Ltd.) copolymerized polyamide 6 / 12 (Tg = 47°C, Tm = 128°C)), 49 mass % of m-PE (trade name "Admer NF587" (manufactured by Mitsui Chemicals, Inc.) acid-modified polyethylene (Tg = -24°C, Tm = 121°C)), 10 mass % of a masterbatch (base resin: CoPA1) containing a crystal nucleating agent "MICRO ACE P-8", and 30 mass % of a masterbatch (base resin: CoPA1) containing an anti-blocking agent "SILTON JC-70". The adhesive layer (100% by mass) contained 49% by mass of CoPA1 (including components derived from the base resin), 0.5% by mass of a crystal nucleating agent, and 1.5% by mass of an anti-blocking agent. The intermediate layer used a raw material obtained by dry-blending LLDPE and OBC at 50% by mass, respectively, the adhesive layer used m-PE, and the outer layer used H-TPAE, which were extruded from a multi-layer annular die to obtain a multi-layer film with a thickness of 10 μm by an inflation method.

[0154] A plain woven fabric was woven using nylon 66 yarn having a fineness of 470 dtex and a single yarn number of 136 using a water jet loom, and then scouring and drying were performed.

[0155] (calendering, lamination)

[0156] One surface of the woven fabric was flattened by calendaring using a heater roll and a resin roll at a temperature of 135° C. and a linear pressure of 2.0 kN / cm.

[0157] Next, the multilayer film was stacked on the flattened fabric side and bonded by lamination. The lamination conditions at this time are as follows.

[0158] Temperature: 160℃

[0159] Roller speed: 15m / min

[0160] Line pressure: 0.5kN / cm

[0161] The warp and weft density of the obtained base fabric is 49 strands / inch, and the unit area weight of the multilayer film is 10g / m 2 Other physical properties of the base fabric are shown in Table 1 below.

[0162] [Example 2]

[0163] The weaving density of the base fabric is 46 threads / inch, and the unit area weight of the multilayer film is 20g / m 2 , except for this, a base fabric was produced in the same manner as in Example 1. The physical properties of the obtained base fabric are shown in Table 1 below.

[0164] [Example 3]

[0165] The unit weight of the multilayer film is 30g / m 2 , except for this, a base fabric was produced in the same manner as in Example 1. The physical properties of the obtained base fabric are shown in Table 1 below.

[0166] [Example 4]

[0167] The base fabric was produced in the same manner as in Example 1 except that the warp and weft weave density of the base fabric was 54 yarns / inch. The physical properties of the obtained base fabric are shown in Table 1 below.

[0168] [Example 5]

[0169] The number of single yarns of the original yarn is 72, the warp and weft density of the base fabric is 46 yarns / inch, and the unit area weight of the multilayer film is 20g / m 2 , except for this, a base fabric was produced in the same manner as in Example 1. The physical properties of the obtained base fabric are shown in Table 1 below.

[0170] [Example 6]

[0171] The fineness of the original yarn is 350dtex, the weaving density of the warp and weft of the base fabric is 58 strands / inch, and the unit area weight of the multilayer film is 20g / m 2 , except for this, a base fabric was produced in the same manner as in Example 1. The physical properties of the obtained base fabric are shown in Table 1 below.

[0172] [Example 7]

[0173] The fineness of the original yarn is 350dtex, the weaving density of the warp and weft of the base fabric is 60 strands / inch, and the unit area weight of the multilayer film is 30g / m 2 , except for this, a base fabric was produced in the same manner as in Example 1. The physical properties of the obtained base fabric are shown in Table 1 below.

[0174] [Example 8]

[0175] A base fabric was produced in the same manner as in Example 1 except that the linear pressure during calendering of the fabric was 0.8 kN / cm and the weaving density of the warp and weft of the base fabric was 46 yarns / inch. The physical properties of the obtained base fabric are shown in Table 2 below.

[0176] [Example 9]

[0177] The linear pressure of the fabric during calendering is 5.0 kN / cm, and the unit area weight of the multilayer film is 20 g / m2 , except for this, a base fabric was produced in the same manner as in Example 1. The physical properties of the obtained base fabric are shown in Table 2 below.

[0178] [Example 10]

[0179] The unit weight of the multilayer film is 50g / m 2 , except for this, a base fabric was produced in the same manner as in Example 1. The physical properties of the obtained base fabric are shown in Table 2 below.

[0180] [Example 11]

[0181] The linear pressure of the fabric during calendering is 10 kN / cm, and the unit area weight of the multilayer film is 20 g / m 2 , except for this, a base fabric was produced in the same manner as in Example 1. The physical properties of the obtained base fabric are shown in Table 2 below.

[0182] [Example 12]

[0183] The surface and back of the fabric were calendered once at a temperature of 135°C, a linear pressure of 2.0 kN / cm, and a pressure of 15 m / min to flatten both sides of the fabric. The unit weight of the multilayer film was 30 g / m 2 , except for this, a base fabric was produced in the same manner as in Example 1. The physical properties of the obtained base fabric are shown in Table 2 below.

[0184] [Example 13]

[0185] The adhesive layer was prepared in the same manner as in Example 2 except that a raw material obtained by dry-blending 60% by mass of L-TPAE1 (trade name "UBESTA XPA 9055F1" (manufactured by Ube Industries, Ltd.), a low melting point thermoplastic polyamide elastomer (Tg = -4°C, Tm = 164°C), 10% by mass of a masterbatch (base resin: L-TPAE1) containing a crystal nucleating agent "MICRO ACE P-8", and 30% by mass of a masterbatch (base resin: L-TPAE1) containing an anti-blocking agent "SILTON JC-70" was used. The adhesive layer (100% by mass) contained 98% by mass of L-TPAE1 (including components derived from the base resin), 0.5% by mass of the crystal nucleating agent, and 1.5% by mass of the anti-blocking agent. The physical properties of the obtained base fabric are shown in Table 2 below.

[0186] [Example 14]

[0187] The adhesive layer was prepared in the same manner as in Example 2 except that a raw material obtained by dry-blending 60% by mass of L-TPAE2 (trade name "UBESTA XPA 9040F1" (manufactured by Ube Industries, Ltd.), a low melting point thermoplastic polyamide elastomer (Tg = -43°C, Tm = 133°C), 10% by mass of a masterbatch (base resin: L-TPAE2) containing a crystal nucleating agent "MICRO ACE P-8", and 30% by mass of a masterbatch (base resin: L-TPAE2) containing an anti-blocking agent "SILTON JC-70" was used. The adhesive layer (100% by mass) contained 98% by mass of L-TPAE2 (including components derived from the base resin), 0.5% by mass of the crystal nucleating agent, and 1.5% by mass of the anti-blocking agent. The physical properties of the obtained base fabric are shown in Table 2 below.

[0188] [Comparative Example 1]

[0189] The fabric is not flattened by calendaring. The weaving density of the base fabric is 46 strands / inch and the unit weight of the multilayer film is 20g / m 2 , except for this, a base fabric was produced in the same manner as in Example 1. The physical properties of the obtained base fabric are shown in Table 3 below.

[0190] The adhesion between the obtained base fabric and the multilayer film was insufficient, gas leakage from the base fabric and sewn portions was large, and the internal pressure retention during airbag deployment was insufficient.

[0191] [Comparative Example 2]

[0192] The fabric is not subjected to flattening treatment by calendaring, and the weight per unit area of ​​the multilayer film is 10 g / m 2 The base fabric was produced in the same manner as in Example 1 except that the linear pressure during lamination was 1.8 kN / cm. The physical properties of the obtained base fabric are shown in Table 3 below.

[0193] In Comparative Example 2, the linear pressure due to lamination was high, pinholes were generated in the film, and the internal pressure retention during airbag deployment was insufficient.

[0194] [Comparative Example 3]

[0195] The fabric is not subjected to flattening treatment by calendaring, and the weight per unit area of ​​the multilayer film is 45 g / m 2 , except for this, a base fabric was produced in the same manner as in Example 1. The physical properties of the obtained base fabric are shown in Table 3 below.

[0196] The obtained base fabric had a heavy weight per unit area, poor foldability, and insufficient internal pressure retention during airbag deployment.

[0197] [Comparative Example 4]

[0198] The linear pressure of the fabric during calendering is 0.2 kN / cm, the warp and weft density of the base fabric is 46 strands / inch, and the unit area weight of the multilayer film is 20 g / m 2 , except for this, a base fabric was produced in the same manner as in Example 1. The physical properties of the obtained base fabric are shown in Table 3 below.

[0199] The calender line pressure of the obtained base fabric was low, the flattening of the fabric was insufficient, and good internal pressure retention of the airbag could not be obtained.

[0200] [Comparative Example 5]

[0201] Nylon 66 raw yarn with a fineness of 470 dtex and a single yarn number of 136 was used for weaving, refining and drying using a water jet loom. Afterwards, silicone was applied using a scraper and heat-treated to crosslink the silicone to produce a coated base fabric. The warp and weft density of the obtained base fabric was 46 yarns / inch, and the unit weight of the silicone resin was 25g / m 2 Other physical properties of the base fabric are shown in Table 3 below.

[0202] The obtained base fabric had large gas leakage due to the mesh openings of the base fabric and sewn portions, and the internal pressure retention during airbag deployment was insufficient.

[0203] [Comparative Example 6]

[0204] The adhesive layer was prepared in the same manner as in Example 2 except that a raw material obtained by dry-blending 60% by mass of m-PE (trade name "Admer NF587" (manufactured by Mitsui Chemicals, Inc.) acid-modified polyethylene (Tg = -24°C, Tm = 121°C), 10% by mass of a masterbatch (base resin: m-PE) containing a crystal nucleating agent "MICRO ACE P-8", and 30% by mass of a masterbatch (base resin: m-PE) containing an anti-blocking agent "SILTON JC-70" was used. The m-PE contained in the adhesive layer (100% by mass) was 98% by mass (including components derived from the base resin), the crystal nucleating agent was 0.5% by mass, and the anti-blocking agent was 1.5% by mass. The physical properties of the obtained base fabric are shown in Table 3 below.

[0205] [Example 15]

[0206] The base fabric prepared in the same manner as in Example 1 was perforated with a sewing machine and the static air permeability was measured. The results are shown in Table 4 below.

[0207] [Example 16]

[0208] The base fabric prepared in the same manner as in Example 8 was perforated with a sewing machine and the static air permeability was measured. The results are shown in Table 4 below.

[0209] [Comparative Example 7]

[0210] The base fabric prepared in the same manner as in Comparative Example 3 was perforated with a sewing machine and the static air permeability was measured. The results are shown in Table 4 below.

[0211] The obtained base fabric had local film peeling due to the sewing needle, and the air permeability was deteriorated.

[0212] [Table 1]

[0213]

[0214] [Table 2]

[0215]

[0216] [Table 3]

[0217]

[0218] [Table 4]

[0219]

Table 4

[0220]

[0221] Industrial Applicability

[0222] If the airbag base fabric described in the present invention is used to make an airbag buffer, the mesh of the base fabric and the sewn parts under high pressure is suppressed, forming an airbag buffer with excellent air tightness and pressure resistance. In addition, an airbag buffer with excellent storage properties and light weight is formed, making it a base fabric for airbags that is suitable for uses such as side curtain airbags, pedestrian airbags, and far side airbags that require internal pressure retention and storage properties.

[0223] Description of Reference Numerals

[0224] #1 Sewing Needle Piercing Thread

[0225] #2 Needlehole Line Center

[0226] #3 Diameter measurement (air permeability evaluation machine)

[0227] #4 Measuring Head

[0228] #5 Determination of the base

[0229] #6 Base Fabric

[0230] #7 Base fabric bending part

[0231] 1 Side curtain airbag

[0232] 2 Sewing part (bag border)

[0233] 3. Inflator installation part

[0234] 4 Inner tube

[0235] 5 Opening

[0236] 6 Joint

[0237] 7 Multilayer film in the center of the protection area

[0238] 11 Yarn (warp or weft)

[0239] 12 Ends in the yarn width direction

[0240] 12' End of yarn width

[0241] 13 Center of yarn width

[0242] A The distance from the bottom of the warp or weft yarn in the width direction to the surface of the multilayer film

[0243] B The distance from the multilayer film surface at the end of the warp or weft in the width direction to the height of the multilayer film surface at the center in the width direction.

Claims

1. A base fabric for an airbag, wherein at least one side of the fabric is covered with a multilayer film having an adhesive layer, the average value of the slip resistance of the base fabric in warp and weft is 450 N / 2.5 cm or more and 1000 N / 2.5 cm or less, and the high-pressure air permeability of the base fabric at 300 kPa is 1.0 L / cm 2 / min or less, and the adhesive layer of the multi-layer film contains a polyamide-based resin.

2. The airbag base fabric according to claim 1, in, The total fineness of the fibers constituting the base fabric for an airbag is 200 dtex to 600 dtex.

3. The base fabric for an air bag according to claim 1, in, The total fineness of the fibers constituting the base fabric for an airbag is 300 dtex to 500 dtex.

4. The base fabric for an air bag according to claim 1, in, The single yarn fineness of the fiber constituting the base fabric for an airbag is 2.0 dtex to 7.0 dtex.

5. The base fabric for an air bag according to claim 1, in, The single yarn fineness of the fiber constituting the base fabric for an airbag is 2.0 dtex to 4.0 dtex.

6. The base fabric for an air bag according to claim 1, in, The average value of the slip resistance of the base fabric in the warp and weft is 450 N / 2.5 cm or more and 950 N / 2.5 cm or less.

7. The base fabric for an air bag according to claim 1, in, The ratio of the thickness of the curved portion of the base fabric for an air bag to the thickness of two overlapping sheets (thickness of the curved portion / thickness of two overlapping sheets) is 2.0 or less.

8. The base fabric for an air bag according to claim 1, in, The ratio of the thickness of the curved portion of the base fabric for an air bag to the thickness of two overlapping sheets (thickness of the curved portion / thickness of two overlapping sheets) is 1.8 or less.

9. The base fabric for an air bag according to claim 1, in, The ratio of the thickness of the curved portion of the base fabric for an air bag to the thickness of two overlapping sheets (thickness of the curved portion / thickness of two overlapping sheets) is 1.7 or less.

10. The base fabric for an air bag according to claim 9, in, The high-pressure air permeability of the airbag base fabric at 300 kPa is 0.8 L / cm 2 / min or less.

11. The base fabric for an air bag according to claim 9, in, The high-pressure air permeability of the airbag base fabric at 300 kPa is 0.7 L / cm 2 / min or less.

12. The base fabric for an air bag according to claim 1 or 2, in, The base fabric for an air bag is scratched more than 600 times after being treated under high temperature and high humidity conditions of 80° C. and 95% for 400 hours.

13. The base fabric for an air bag according to claim 12, in, The number of scratches is 800 or more.

14. The base fabric for an air bag according to claim 12, in, The number of scratches is 1000 or more.

15. The base fabric for an air bag according to claim 1 or 2, in, The base fabric for an air bag has a cover factor of 1800 or more and 2400 or less.

16. The base fabric for an air bag according to claim 15, in, The base fabric for an air bag has a cover factor of 1900 or more and 2300 or less.

17. The base fabric for an air bag according to claim 16, in, The airbag base fabric has a cover factor of 2200 or less.

18. The base fabric for an air bag according to claim 1 or 2, in, The static air permeability of the base fabric for the airbag when a sewing needle passes through is 0.30 L / dm 2 / min or less.

19. The base fabric for an air bag according to claim 1 or 2, in, For the cross-section obtained by cutting the warp yarn exposed in the surface of the airbag base fabric covered with the multilayer film at the center of the warp direction of the exposed part, or the cross-section obtained by cutting the weft yarn exposed in the surface of the airbag base fabric covered with the multilayer film at the center of the weft direction of the exposed part, when observing using SEM, and setting the distance from the bottom of the yarn in the center of the width direction of the warp yarn or the weft yarn to the surface of the multilayer film as A, and setting the distance from the surface of the multilayer film at the end of the width direction of the warp yarn or the weft yarn to the height of the multilayer film surface in the center of the width direction as B, the base fabric cross-sectional thickness ratio B / A is greater than 0.2 and less than 0.

6.

20. The base fabric for an air bag according to claim 19, in, The base fabric cross-sectional thickness ratio B / A is greater than or equal to 0.25 and less than or equal to 0.

55.

21. The base fabric for an air bag according to claim 19, in, The base fabric cross-sectional thickness ratio B / A is greater than or equal to 0.30 and less than or equal to 0.

50.

22. The base fabric for an air bag according to claim 1 or 2, in, The unit area weight of the multilayer film is 5 to 30 g / m 2 .

23. The base fabric for an air bag according to claim 22, in, The unit area weight of the multilayer film is 5 to 25 g / m 2 .

24. The base fabric for an air bag according to claim 22, in, The unit area weight of the multilayer film is 5 to 20 g / m 2 .

25. The base fabric for an air bag according to claim 22, in, The unit area weight of the multilayer film is 5 to 15 g / m 2 .

26. The base fabric for an air bag according to claim 1, in, The viscosity of the polyamide resin is 50 to 200 ml / g.

27. The base fabric for an air bag according to claim 1, in, The viscosity of the polyamide resin is 80 to 180 ml / g.

28. The base fabric for an air bag according to claim 1, in, The viscosity of the polyamide resin is 100 to 150 ml / g.

29. The base fabric for an air bag according to claim 1, in, The polyamide-based resin is copolymerized polyamide.

30. The base fabric for an air bag according to claim 1, in, The melting point of the polyamide resin is 100 to 160°C.

31. The base fabric for an air bag according to claim 1, in, The melting point of the polyamide resin is 110 to 150°C.

32. The base fabric for an air bag according to claim 1, in, The melting point of the polyamide resin is 120-140°C.

33. The base fabric for an air bag according to claim 1, in, The glass transition temperature of the polyamide resin is 0 to 80°C.

34. The base fabric for an air bag according to claim 33, in, The glass transition temperature of the polyamide resin is 10 to 70°C.

35. The base fabric for an air bag according to claim 33, in, The glass transition temperature of the polyamide resin is 20 to 60°C.

36. An airbag comprising the base fabric for an airbag according to any one of claims 1 to 35.

37. A side curtain airbag comprising the base fabric for an airbag according to any one of claims 1 to 35.

38. A pedestrian airbag comprising the base fabric for an airbag according to any one of claims 1 to 35.

39. A distal airbag comprising the base fabric for an airbag according to any one of claims 1 to 35.